Aortic Valve Annular Sizing: Intraoperative Assessment Versus Preoperative Multidetector Computed Tomography. (May 2017) - George, Isaac; Guglielmetti, Laura C.; Bettinger, Nicolas; Moss, Andrew; Wang, Catherine; Kheysin, Nathan; Hahn, Rebecca; Kodali, Susheel; Leon, Martin; Bapat, Vinayak; Borger, Michael A.; Williams, Mathew; et al.
Abstract : Background—: Appropriate valve sizing is critical in aortic valve replacement. We hypothesized that direct intraoperative valve sizing results in smaller aortic annular diameters compared with sizing based on systolic-phase multidetector computerized tomographic (MDCT) imaging. Methods and Results—: We retrospectively analyzed 78 patients undergoing surgical aortic valve replacement for severe aortic stenosis between 2012 and 2014 at our institution. Preoperative MDCT measurements of the aortic annulus served as basis for assignment to a theoretical surgical valve size, which was then (1) compared to the implanted valve size and (2) to a theoretical transcatheter aortic valve replacement valve size. To quantify the resulting differences, geometric orifice areas (GOA) were calculated. MDCT-based sizing produced the same valve size for n=34 patients (group CT-same), a larger valve with a 25% increased GOA in n=32 patients (group CT-Lg) and a smaller GOA by 22% in n=12 patients (group CT-Sm). On the basis of MDCT measurements, 41% of valves implanted were undersized. The comparison of intraoperative implanted to a theoretical transcatheter aortic valve replacement valve size resulted in GOAs 25% larger for patients in group CT-same, 40.6% larger in group CT-Lg and 14.6% larger in group CT-Sm. Conclusions—: Preoperative MDCT measurements differ substantially from direct intraoperative assessment of the aortic annulus. Implanted surgical aortic valve replacement valves were smaller relative to MDCT-based sizing in 41% of patients, and the potential GOA was between 25% and 40.6% larger if patients had undergone transcatheter aortic valve replacement. Abstract : Supplemental Digital Content is available in the text.